The Effect of Firing Line Models Containing On Learning Competencies of Eight Grade Students at Junior High School 33 Padang - Vivin Novelyani; Helendra Helendra; Sa'diatul Fuadiyah; Ramadhan Sumarmin (Universitas Negeri Padang, 2019)
This research is based on the problems that exist in Padang 33 SMP 33, namely the learning model that is less varied, the learning competency of students is still low. Efforts that can be done are applying the firing line learning model on pests and diseases in plants at 33 SMP Negeri Padang. The purpose of this study was to determine the effect of the application of the firing line learning model on the learning competencies of Grade VIII students of SMP 33 Padang. This type of research is experimental research with a randomized control group posttest only design. The population in this study were all class VIII SMP 33 Padang which were registered in the 2018/2019 Academic Year totaling six classes. Sampling was done using purposive sampling technique, which was chosen as the sample of the study was class VIII.1 as the experimental class and class VIII.2 as the control class. The instruments used were in the form of posttest questions for knowledge competencies, observation sheets for attitude and skills competencies. Based on the results of the study using the t-test, it can be concluded that the knowledge competencies of students t count 3.02> t table 1.67, the competency attitudes tcount 5.38> t table 1.67, and competence skills t count 4.39 > t table 1.67. This shows that the hypothesis is accepted. So, it can be concluded that the application of the firing line learning model can improve the competency of knowledge, attitudes, and skills of class VIII students of SMP 33 Padang